Plasmodium falciparum-Infected Erythrocytes Induce Granzyme B by NK Cells through Expression of Host-Hsp70 - Böttger, Evelyn (Public Library of Science, 2012)
In the early immune response to Plasmodium falciparum-infected erythrocytes (iRBC), Natural Killer (NK) cells are activated, which suggests an important role in innate anti-parasitic immunity. However, it is not well understood whether NK cells directly recognize iRBC or whether stimulation of NK cells depends mainly on activating signals from accessory cells through cell-to-cell contact or soluble factors. In the present study, we investigated the influence of membrane-bound host Heat shock protein (Hsp) 70 in triggering cytotoxicity of NK cells from malaria-naïve donors or the cell line NK92 against iRBC. Hsp70 and HLA-E membrane expression on iRBC and potential activatory NK cell receptors (NKG2C, CD94) were assessed by flow cytometry and immunoblot. Upon contact with iRBC, Granzyme B (GzmB) production and release was initiated by unstimulated and Hsp70-peptide (TKD) pre-stimulated NK cells, as determined by Western blot, RT-PCR and ELISPOT analysis. Eryptosis of iRBC was determined by Annexin V-staining. Our results suggest that presence of Hsp70 and absence of HLA-E on the membrane of iRBC prompt the infected host cells to become targets for NK cell-mediated cytotoxicity, as evidenced by impaired parasite development. Contact of iRBC with NK cells induced release of GzmB. We propose that following GzmB uptake, iRBC undergo eryptosis via a perforin-independent, GzmB-mediated mechanism. Since NK activity toward iRBC could be specifically enhanced by TKD peptide and abrogated to baseline levels by blocking Hsp70 exposure, we propose TKD as an innovative immunostimulatory agent to be tested as an adjunct to anti-parasitic treatments in vivo.